Complete Genome Sequence of wBp, the Wolbachia Endosymbiont of Brugia pahangi FR3 - Lebov, Jarrett F. (Microbiol Resour Announc, 2020)
Lymphatic filariasis is a devastating disease caused by filarial nematode roundworms, which contain obligate Wolbachia endosymbionts. Here, we assembled the genome of wBp, the Wolbachia endosymbiont of the filarial nematode Brugia pahangi, from Illumina, Pacific Biosciences, and Oxford Nanopore data. The complete, circular genome is 1,072,967 bp.